Self-regulation-based learning and mathematical literacy: Exploring the ability of students at singa putih munfaridin islamic boarding school in solving HOTS problems - Syafitri, Risma Widya Hadi; Lestari, Nurcholif Diah Sri; Putri, Inge Wiliandani Setya; Pambudi, Didik Sugeng; Murtikusuma, Randi Pratama (Mahesa Research Center, 2025)
Mathematics is an important foundation in developing critical and logical thinking skills, which are reflected through mathematical literacy. However, PISA 2022 scores show that Indonesian students' mathematical literacy is still below the international average, with the main weakness in solving HOTS questions. This qualitative research aims to analyze the relationship between self-regulated learning (SRL) and students' mathematical literacy in solving HOTS problems related to System of Linear Equations of Three Variables (SPLTV) at Singa Putih Munfaridin Islamic Boarding School, Pasuruan. Data were collected through HOTS tests, SRL questionnaires, and interviews with grade X students who were grouped into three SRL categories: low, medium, and high. The results showed that students with high SRL could formulate problems efficiently, apply systematic strategies, and interpret solutions independently. Medium SRL students have difficulty in applying concepts due to inaccuracy and also fail to independently verify solutions, with conclusions often adapted from classmates. Low SRL students only reached the formulation stage and failed at the application and interpretation stages. These findings reinforce Zimmerman & Schunk's theory that SRL involves a cycle of planning, monitoring and self-evaluation.